2020
DOI: 10.1007/s11573-020-01006-9
|View full text |Cite
|
Sign up to set email alerts
|

Linking actual self-congruence, ideal self-congruence, and functional congruence to donor loyalty: the moderating role of issue involvement

Abstract: Nonprofit organizations need loyal donors to accomplish their mission and goals. However, organizations lose up to 60% of their first-time donors. Therefore, a deeper understanding of the determinants of donor loyalty is necessary. This study tests whether actual self-congruence, ideal self-congruence, and functional congruence strengthen the tie between nonprofit organizations and donors. In addition, and as an extension of the self-congruence theory, issue involvement is added as a moderator variable. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 66 publications
(175 reference statements)
3
27
0
Order By: Relevance
“…Contrary to previous research, it was observed that the construct of fearedself had a beneficial impact on cigarette butts littering behaviour, and that the congruence of the feared self and landfill knowledge did not help reduce cigarette butts littering behaviour (Gatersleben et al, 2019;Mathiyazhagan et al, 2018). Recent studies examined the moderating effect of social awareness (Kaufmann et al, 2016;Mathiyazhagan Zogaj et al, 2021), and this effect was consistent with previous research findings (Baptiste, 2008;Kollmuss & Agyeman, 2002;Kollmuss & Agyeman, 2002;Rasool et al, 2021;Xu et al, 2013). As for the originality of our research outcomes, they shed new light on the landfill awareness context by demonstrating that it is occasionally a strong driver.…”
Section: Discussionmentioning
confidence: 77%
“…Contrary to previous research, it was observed that the construct of fearedself had a beneficial impact on cigarette butts littering behaviour, and that the congruence of the feared self and landfill knowledge did not help reduce cigarette butts littering behaviour (Gatersleben et al, 2019;Mathiyazhagan et al, 2018). Recent studies examined the moderating effect of social awareness (Kaufmann et al, 2016;Mathiyazhagan Zogaj et al, 2021), and this effect was consistent with previous research findings (Baptiste, 2008;Kollmuss & Agyeman, 2002;Kollmuss & Agyeman, 2002;Rasool et al, 2021;Xu et al, 2013). As for the originality of our research outcomes, they shed new light on the landfill awareness context by demonstrating that it is occasionally a strong driver.…”
Section: Discussionmentioning
confidence: 77%
“…In cognitive self-assessment, people often desire to maintain consistency between cognitions (Gawronski and Strack, 2012), such as unity between perceptions and beliefs. Self-congruity is a perception process where a customer feels a connection with a brand prior to evaluation (Zogaj et al, 2020). Positive (or negative) perceptions affect positive (or negative) beliefs about the brand (Bitner, 1992).…”
Section: Direct Effectsmentioning
confidence: 99%
“…Previous studies have explored the impact of self-congruity on tourist evaluations such as tourist satisfaction (TS) (Kumar, 2016; Kim and Thapa, 2018; Ranjbarian and Ghaffari, 2018) and behaviors such as destination brand loyalty (DBL) (Ardyan and Wibisono, 2019; Kang et al , 2015; Kim and Thapa, 2018). The impact of self-congruity on destination loyalty has mostly been evaluated as a direct effect (Kang et al , 2015; Frias et al , 2020; Zogaj et al , 2020). However, brand loyalty, from the first stage of the perception of self-congruity to the final stage of tourist loyalty to the destination, might not be a straightforward process.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the seller may signal the relevance of one of those motives (described above) for donations by tying the donations to the tips and customers' payments may positively be affected because of the desire for actual or ideal self-congruence. Zogaj et al (2021) also outline that self-congruence may be subconsciously formed and affects functional congruence subsequently, i.e. the perceived similarity of expected product characteristics with its realization.…”
Section: Related Literature and Predictionsmentioning
confidence: 97%
“…Within SSR, these personal costs are given for the seller and, therefore, customers might positively reciprocate towards these altruistic preferences by paying higher amounts. Zogaj et al (2021) provide an interesting framework based on consumer psychology research to structure customer behavior which we apply to our specific setting in the following. They indicate that donors' behavior may be influenced by how much each person's image of her-/himself, i.e., the self-concept, matches the self-concept of another individual or entity.…”
Section: Related Literature and Predictionsmentioning
confidence: 99%